2020
DOI: 10.1177/1932296820932186
|View full text |Cite
|
Sign up to set email alerts
|

Unintended Consequence of High-Dose Vitamin C Therapy for an Oncology Patient: Evaluation of Ascorbic Acid Interference With Three Hospital-Use Glucose Meters

Abstract: The use of high-dose vitamin C in cancer care has offered promising results for some patients. However, the intravenous (IV) doses used for these patients can reach concentrations that interfere with some strip-based glucose meters. We characterized the impact of vitamin C interference, from standard to the very high doses used for some cancer protocols, using three different hospital-use glucose meters. For two of the three devices tested, increasing concentrations of ascorbic acid caused false elevations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…Intriguingly, the current study revealed a phenomenon of blood glucose measurement interference, in consistent with previous studies [ 30 32 ]. Our glucose-monitoring device adopted glucose oxidase method.…”
Section: Discussionsupporting
confidence: 93%
“…Intriguingly, the current study revealed a phenomenon of blood glucose measurement interference, in consistent with previous studies [ 30 32 ]. Our glucose-monitoring device adopted glucose oxidase method.…”
Section: Discussionsupporting
confidence: 93%
“…Of these, only the Nova StatStrip glucose meter specifically gave an "error" result for glucose readings that prompted clinicians to confirm POC-BG values with a venous blood sample. 9 There are various sources of error in measuring POC-BG and these can pose a safety hazard to patient care. Chemical interference with the BG meter strip is only one of these.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, only the Nova StatStrip glucose meter specifically gave an “error” result for glucose readings that prompted clinicians to confirm POC-BG values with a venous blood sample. 9 …”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] In studies that have been performed with systems for SMBG evaluating the impact of high doses of ascorbic acid application in oncology patients or patients with sepsis, some fail with high ascorbic acid levels in blood while others do not. [17][18][19] However, this may not be relevant for CGM systems as it is not known how high the corresponding levels of ascorbic acid are in the ISF. It is possible that ascorbic acid circulates into the ISF in the same way that glucose does because this vitamin has a similar structure to glucose.…”
Section: Abbott-ascorbic Acidmentioning
confidence: 99%